Design and development of a low-cost two-point bending tester for bamboo culm sheaths - Indraswari Kusumaningtyas; Jalu Akbar Wirabuana; Al Hafid Baharsyah; Gea Oswah Fatah Parikesit (Prosiding SNTTM, 2025)
Sound generation in musical instruments depends on the instrument’s material properties. This is not yet completely understood for the bundengan musical instrument because the material properties of the bamboo culm sheath (slumpring in Javanese) that covers the bundengan’s woven structure are unknown. The dominant vibration mode of the bundengan is transversal; thus, the bending modulus of elasticity is required. Bamboo culm sheaths are thin, lightweight, and relatively fragile, so they must be characterised by a bending tester that can deliver a small enough force at a constant deflection rate. This is essential to obtain sufficient data within the material’s elastic region before the bamboo culm sheath breaks. It was observed that there are similarities between the structure of bamboo culm sheaths and corrugated paperboard. Therefore, a two-point bending tester was designed and developed based on the bending test standards of paper and paperboard. The design process comprises needs identification, design specification, and conceptual, preliminary, and detailed design. A prototype was then developed, calibrated, and tested. Tests with specimens made from thin aluminium plates gave a bending modulus of 75.15±5.90 GPa and 74.59±2.55 GPa for deflection angles of 5.4° and 15.3°, respectively. This indicates that the two-point bending tester can perform repeated tests with relatively good precision and accuracy, so that it can be further used to test bamboo culm sheaths.